2006
DOI: 10.1089/neu.2006.23.962
|View full text |Cite
|
Sign up to set email alerts
|

Severe Human Traumatic Brain Injury, but Not Cyclosporin A Treatment, Depresses Activated T Lymphocytes Early after Injury

Abstract: Severe traumatic brain injury (TBI) leads to an immunocompromised state responsible for an increased morbidity and mortality. Our understanding of the mechanisms responsible for this brain damage is incomplete. Damage maybe mediated by a complex cascade of neuroinflammation, and cytokine activation. In addition, translocation and accumulation of T cells in the brain parenchyma could take place and be related to detrimental effects. Our aims in this prospective randomized pilot study, were to detect the early e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 47 publications
2
29
0
1
Order By: Relevance
“…These findings mirror those reported in a previous article, in which we clearly demonstrated that no significant difference exists in the studied immunologic parameters in the placeboversus CsA-treated groups at any time point (Mazzeo et al, 2006). Furthermore, we could not demonstrate any other significant covariable factors in the incidence of lung infections after admission, other than the early impairment of T-cell activation secondary to injury that was not due to the administration of CsA (Mazzeo et al, 2006).…”
Section: Infectious Complicationssupporting
confidence: 91%
See 2 more Smart Citations
“…These findings mirror those reported in a previous article, in which we clearly demonstrated that no significant difference exists in the studied immunologic parameters in the placeboversus CsA-treated groups at any time point (Mazzeo et al, 2006). Furthermore, we could not demonstrate any other significant covariable factors in the incidence of lung infections after admission, other than the early impairment of T-cell activation secondary to injury that was not due to the administration of CsA (Mazzeo et al, 2006).…”
Section: Infectious Complicationssupporting
confidence: 91%
“…The administration of any medication that might induce further immunological suppression should therefore be undertaken with caution, in order to avoid any additional or synergistic suppression of immune function after severe TBI. We have previously reported that there were no significant differences between the placebo-and CsAtreated patients in this clinical trial with regard to immunological parameters, such as total lymphocyte count and phenotypic cell subsets (CD3 þ mature T cells, CD4 þ helper= inducer T cells, and CD8 þ suppressor=cytotoxic T cells), or the incidence of infection (Mazzeo et al, 2006). No significant difference was seen in the incidence of infection or sepsis between the two study groups detailed here.…”
Section: Effects Of Csa On Blood Counts and Incidence Of Infectionmentioning
confidence: 45%
See 1 more Smart Citation
“…The importance of noninvasive methods to detect and quantify axonal injury is underscored by ongoing trials of neuroprotectants such as cyclosporin A (Empey et al, 2006;Mazzeo et al, 2006) and hypothermia (Adelson et al, 2005) that are aimed at least in part at reducing axonal injury Koizumi and Povlishock, 1998;Okonkwo et al, 1999;Scheff and Sullivan, 1999). Stratification of patients based on the presence or severity of axonal injury could significantly improve the design of such trials.…”
Section: Discussionmentioning
confidence: 99%
“…Encouraged by these laboratory data, further studies were performed to provide pharmacological guidelines to further clinical studies 19,20 and to establish the safety of the drug in respect with its immunosuppressive properties. 20,21 Based on these data, a prospective randomized and placebo-controlled, double-blinded two-center clinical study was performed in severe human TBI. During the study, patients suffering some severe TBI were enrolled and received 5 mg/kg during a 24-hour period, delivered within 12 hours from injury.…”
Section: Mitochondrial Permeability Transitionmentioning
confidence: 99%